2017
DOI: 10.1093/jxb/erx304
|View full text |Cite
|
Sign up to set email alerts
|

Phytosiderophores determine thresholds for iron and zinc accumulation in biofortified rice endosperm while inhibiting the accumulation of cadmium

Abstract: We unravel the mechanisms that set upper limits for iron and zinc accumulation in rice endosperm while inhibiting the accumulation of cadmium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 77 publications
(136 reference statements)
1
32
0
Order By: Relevance
“…There was no correlation between NA and metals, whereas several correlations between metals were found, including Mn vs. Zn ( r = 0.782; P ≤ 0.01), Mn vs. Cu ( r = 0.725; P ≤ 0.01) and Fe vs. Zn ( r = 0.566; P ≤ 0.05). Correlations between Fe and Zn have been found in previous studies ( Lombi et al, 2011 ; Anuradha et al, 2012 ; Banakar et al, 2017b ; Kampuang et al, 2017 ), and are expected due to the fact that both metals share mechanisms for uptake, short- and long-distance transport in the plant and intracellular trafficking.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…There was no correlation between NA and metals, whereas several correlations between metals were found, including Mn vs. Zn ( r = 0.782; P ≤ 0.01), Mn vs. Cu ( r = 0.725; P ≤ 0.01) and Fe vs. Zn ( r = 0.566; P ≤ 0.05). Correlations between Fe and Zn have been found in previous studies ( Lombi et al, 2011 ; Anuradha et al, 2012 ; Banakar et al, 2017b ; Kampuang et al, 2017 ), and are expected due to the fact that both metals share mechanisms for uptake, short- and long-distance transport in the plant and intracellular trafficking.…”
Section: Resultssupporting
confidence: 66%
“…Other rice transgenics complying with this DMA/NA scenario are those overexpressing OsNAS1-3 ( Lee et al, 2009b ) or HvNAS1 alone ( Masuda et al, 2009 ), as well as OsNAS2 in combination with SoyferH1 ( Trijatmiko et al, 2016 ), which showed concentration increases in polished seeds (endosperm) of 2- to 33-fold for DMA, 5- to 32-fold for NA, 2.0- to 7.5-fold for Fe and 2.2- to 3.8-fold for Zn. The same scenario occurs when overexpressing OsNAS1 in combination with HvNAATb ( Banakar et al, 2017b ), leading to increases in polished seeds of 33-, 160-, 4.0-, and 4.1-fold for DMA, NA, Fe, and Zn concentrations, respectively; that study also shows an increased abundance of NA and DMA in leaves and roots, which promotes Fe and Zn uptake, root-to-shoot translocation, and finally seed loading. Other transgenics also showed concomitant Fe and Zn concentration increases, but the DMA and/or NA concentrations were not determined ( Wirth et al, 2009 ; Boonyaves et al, 2017 ; Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations